Synergistic Minds: Exploring the Cultural Reimagining of Creativity and Problem-Solving Through Symbiotic Human-AI Teams in Advanced Manufacturing - Mistarihi, Mahmoud Z.; M, Aruna (Journal of Posthumanism, 2025)
This paper explores the profound cultural transformations instigated by symbiotic human-synthetic intelligence (AI) teams inside Industry 5.0, focusing on the implications of deep cognitive partnerships in advanced production. It investigates the complex interplay among human employers, technological affordances, and organizational systems, moving the point of interest to the profound implications of those deep cognitive partnerships to reshape the cultural landscape of work and advanced production. By reading the theoretical foundations, ethical considerations, and societal capability effects, this provides a look at goals to develop the conversation beyond mere performance and productivity, exploring how symbiosis reshapes work practices, alters power dynamics, and redefines human capabilities and understanding in the generation of intelligent machines. Ultimately, it seeks to illuminate how these partnerships impact performance and output and reshape human roles, redistribute authority, and redefine the essence of human skills and expertise in an era increasingly shaped by clever automation, emphasizing the cultural negotiations inherent in this evolution.